Facilely fabricating Mg, Ca modified Co based ordered mesoporous catalysts for CO2 reforming of CH4: The effects of basic modifiers. (19th October 2016) - Xu, Leilei; Zhang, Xing; Chen, Mindong; Qi, Lu; Nie, Dongyang; Ma, Yinghui
Abstract: Co based catalysts have been widely investigated as the catalysts for carbon dioxide reforming of methane (CRM) reaction due to outstanding coke-resistant capacity. Herein, a series of Co based ordered mesoporous materials incorporated with Mg and Ca basic modifiers had been designed and fabricated by facile evaporation induced self-assembly (EISA) strategy. The obtained materials were systematically characterized by X-ray diffraction (XRD), N2 adsorption–desorption analysis, transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), H2 temperature programmed reduction (H2- TPR), and CO2 temperature programmed desorption (CO2 -TPD). The characterization results demonstrated that these materials calcined at 700 °C possessed relatively large surface areas (130.0–150.0 m 2 /g), big pore volume (0.30 cm 3 /g), narrow pore size distribution (9.5–11.0 nm), and uniform mesoporous channels. Due to these good textural properties and unobstructed mesoporous channels, these materials could accommodate the gaseous reactants with sufficiently accessible Co active sites, thus showing high catalytic activity toward CRM reaction. Besides, the Co active centers were in situ incorporated into and stabilized by the mesoporous framework. Therefore, the thermal agglomeration of the metallic Co nanoparticles during the CRM reaction could be effectively suppressed, displaying excellent catalytic stability. For the Mg and Ca basic modifiers, their incorporation greatly strengthened the surface basicity and intensified the chemisorption of CO2, which would be helpful in accelerating the surface coke elimination process. Therefore, these Co based ordered mesoporous materials incorporated with Mg and Ca basic modifiers could be considered as potential catalysts for CRM reaction. Graphical abstract: Highlights: Mg, Ca modified ordered mesoporous Co based catalysts synthesized by EISA method. Materials with excellent textural properties and thermal stabilities. Mg, Ca modifiers improve the catalytic performance and decrease the surface coke. Basic modifiers lower the apparent activation energies of CO2 and CH4 reactants.